A New Open Loop Approach for Identifying the Initial Rotor Position of a Permanent Magnet Synchronous Motor - Qixin Zhu; Lei Xiong; Hongli Liu; Yonghong Zhu; Guoping Zhang (Journal of Control Science and Engineering)
The precision of initial rotor position detection is critical for the start and running performance of permanent magnet synchronous motor (PMSM). This work describes a new open loop approach for identifying the initial position of a PMSM with an incremental encoder, even when a constant load torque is being applied. By giving a testing current with high frequency to the stator winding, the initial rotor position of a PMSM can be detected with reasonable accuracy. The rotor almost does not move during the process of identification. The FFT algorithms are used to remove the phase bias effects in identification. Our approach is quicker and simpler than the conventional approaches.